2009
DOI: 10.1007/s00380-008-1084-3
|View full text |Cite
|
Sign up to set email alerts
|

Right atrial spontaneous echo contrast indicates a high incidence of perfusion defects in pulmonary scintigraphy in patients with atrial fibrillation

Abstract: This study investigated the relationship between right atrial SEC (RA-SEC) and silent pulmonary embolism (PE) in patients with nonvalvular atrial fibrillation (NVAF). Spontaneous echo contrast (SEC) within the cardiac chambers is associated with an increased risk of thromboembolism. However, most studies have examined the relationship between left atrial SEC and systemic thromboembolic disease. Transesophageal echocardiography (TEE) was performed in 210 patients with NVAF to assess a risk of thromboembolism. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…In patients with right atrial spontaneous echo contrast, silent PE was investigated by using pulmonary scintigraphy [17]. Symptomatic PE and DVT data were not reported, but pulmonary perfusion defects were reported to be significantly increased in patients with spontaneous echo contrast in the RA group versus the controls [17]. In our study, the incidence of asymptomatic PE was 14.1% according to the first observer and 8.5% according to the second observer.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In patients with right atrial spontaneous echo contrast, silent PE was investigated by using pulmonary scintigraphy [17]. Symptomatic PE and DVT data were not reported, but pulmonary perfusion defects were reported to be significantly increased in patients with spontaneous echo contrast in the RA group versus the controls [17]. In our study, the incidence of asymptomatic PE was 14.1% according to the first observer and 8.5% according to the second observer.…”
Section: Discussionmentioning
confidence: 68%
“…During random screening of thorax CT scans performed for reasons other than suspected PE, incidental PE was found in 2.6% of hospitalizations per se, and antecedent cancers were reported as the most important risk factors [9]. In patients with right atrial spontaneous echo contrast, silent PE was investigated by using pulmonary scintigraphy [17]. Symptomatic PE and DVT data were not reported, but pulmonary perfusion defects were reported to be significantly increased in patients with spontaneous echo contrast in the RA group versus the controls [17].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on AF patients has confirmed that PTE is associated with spontaneous echocardiographic contrast in right atria. 7 The pathogenesis of PTE is multifactorial in such cases. Abnormalities of pulmonary vessel wall and blood constituents may contribute to the formation of PTE.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, we almost continuously monitored TEE for evaluation of a right atrial thrombus and early detection of pulmonary thromboembolism but did not observe resolution of a right atrial thrombus. Spontaneous echogenic contrast, keyimage, representing gradual breaking down of a right atrial thrombus, might be helpful to discriminate between its abrupt disappearance and its gradual breaking down, and to count the time from its appearance to its disappearance [18], but unfortunately could not be obtained. The size of the cardiac chamber was in the normal range and not changed before and after abrupt formation and spontaneous resolution of the right atrial thrombus.…”
Section: Discussionmentioning
confidence: 99%